A Novel Circular Complex Picture Fuzzy TOPSIS Framework for Multi-Criteria Breast Cancer Treatment Decision Making - Mani Parimala; D.Arivuoli; R.Jeevitha (The Bioscan, 2026)
Breast cancer treatment planning is a high-stakes multi-criteria decision-making (MCDM) problem in which clinicians must balance clinical effectiveness, toxicity, cost, treatment duration, and patient-centred outcomes under pervasive uncertainty and conflicting expert opinions. Classical TOPSIS and its early fuzzy extensions often cannot simultaneously capture multiple attitudes such as acceptance, rejection, neutrality, and abstention, nor can they flexibly model phase-type or circular uncertainty that arises from time-varying clinical evidence and heterogeneous expert judgements. Recently, circular intuitionistic and circular complex fuzzy structures have been introduced to extend fuzzy membership from a single scalar to a circular or complex-circular domain, thereby enriching the geometric representation of vagueness and hesitancy in MCDM problems.